Mutu Pelayanan Kefarmasian di Puskesmas Kabupaten Cilacap dan Faktor-Faktor yang Mempengaruhi - Sofiah, Siti Asadu; Satibi, Satibi; Wijayanti, Tri (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Pharmaceutical services are integrated activities with the aim of identifying, preventing, solving drug problems, and health-related problems. This study aims to determine the quality of pharmacy services at public health center and the factors that influence it. This observational study was conducted by direct observation of research subjects with document review and interviews to explore the supporting and inhibiting factors in the implementation of pharmacy services at the public health centers in Cilacap Regency. The results showed that for the quality of drug management, of the 25 indicators, what was standardized were drug proposals, items suitability with disease patterns, drug storage, drug availability for one month, empty stock items, insufficient drug items, overstock items, and suitability of physical quantities. drug. For clinical pharmacy services, out of 18 indicators, the standards are service time, drug cost per prescription visit, items per prescription, generic preparations, antibiotics for non-specific diarrhea, ORS and zinc administration for diarrhea, antibiotics for non-pneumonia ISPA, and injection use. Factors of human resources, budget availability, status of puskesmas, and type of puskesmas have no effect on the quality of pharmaceutical services.Keywords: pharmacy; service quality; public health center ABSTRAK Pelayanan kefarmasian merupakan kegiatan yang terpadu dengan tujuan untuk mengidentifikasi, mencegah, menyelesaikan masalah obat, dan masalah yang berhubungan dengan kesehatan. Penelitian ini bertujuan untuk mengetahui mutu pelayanan kefarmasian puskesmas dan faktor-faktor yang mempengaruhinya. Penelitian observasional ini dilakukan dengan observasi langsung terhadap subjek penelitian dengan telaah dokumen dan wawancara untuk menggali faktor pendukung dan penghambat pelaksanaan pelayanan kefarmasian Puskesmas di Kabupaten Cilacap. Hasil penelitian menunjukkan bahwa untuk mutu pengelolaan obat, dari 25 indikator, yang sesuai standar adalah pengusulan obat, kesesuaian item dengan pola penyakit, penyimpanan obat, ketersediaan obat satu bulan, item stok kosong, item obat kurang, item stok berlebih, dan kesesuaian jumlah fisik obat. Untuk pelayanan farmasi klinik, dari 18 indikator, yang sesuai standar adalah waktu pelayanan, biaya obat per kunjungan resep, item per resep, sediaan generik, antibiotik pada diare non-spesifik, pemberian oralit dan zink untuk diare, antibiotik pada ISPA non-pneumonia, dan penggunaan injeksi. Faktor sumber daya manusia, ketersediaan anggaran, status puskesmas, dan tipe puskesmas tidak berpengaruh terhadap mutu pelayanan kefarmasian.Kata kunci: kefarmasian; mutu pelayanan; puskesmas